PEMBERDAYAAN SISWA-SISWI SEKOLAH MENENGAH KEJURUAN NEGERI PERIKANAN DALAM PEMBENIHAN IKAN AIR TAWAR - Akhmad Taufiq Mukti; Muhamad Amin; Putri Desi Wulan Sari; Veryl Hasan; Gunanti Mahasri; Puguh Yugo Wijanarko; Lia Oktavia Ika Putri; Salman Aldo Alfaresi (Jurnal Penamas Adi Buana, 2024)
The limited knowledge and skills in the hatchery technology application of the freshwater fish to seed production business are obstacles faced by prospective young entrepreneurs in the aquaculture sector. The Community Partnership Program (PKM) was provided as a strategic step to overcome the obstacles faced by the target partner group in this PKM activity in line with the Public Vocational Secondary School's (SMKN) expectations to provide sufficient insight into science and technology for SMKN students as provision for independent entrepreneurship. The aim of this PKM was to transfer the application of freshwater fish (catfish) hatchery technology and the produce fish seeds independently. The activity method was conducted through: a) delivery of material and training related to broodstocks selection and gonad maturation, b) training on the application of freshwater fish hatchery technology (catfish), and c) regular monitoring and assistance to PKM target partner groups by involving related agencies (SMKN). Delivery of material was carried out regularly, both online and face to face (offline). Approximately 40 students of SMKN Ngadirojo, Pacitan Regency who took the flagship program of Aquaculture Agribusiness, attended this activity. This PKM activity was also attended by accompanying teachers. The practical results show an increase in the knowledge and skills of partners in catfish hatchery through the application of semi-artificial catfish broodstocks spawning technology.